Haze and inbound tourism: Empirical evidence from China - Wu, Wenzhi; Xia, Xin; Cui, Chunyu; Qiu, Fudong (Frontiers in Psychology, 2023)
The impact of climate change on tourism has always been an important topic for research in the field of international tourism. In recent years, haze has been widely recognized as the primary negative factor affecting the development of inbound tourism in China. In this study, we conduct a theoretical analysis of the mechanism through which haze influences the tourism industry, and then we empirically analyze the impact on China’s inbound tourism using surface particulate matter (PM2.5) concentrations as a proxy for haze, based on provincial panel data from 1998 to 2016. The empirical results show that haze not only has an inhibitory effect on inbound tourism, but it also significantly reduces the average length of stay of international tourists. In addition, while there are significant regional differences in the crowding-out effect of haze pollution on inbound tourism, the effect varies depending on the origin of inbound tourists, exhibiting the greatest negative impact on inbound tourism from Taiwan and the smallest from foreign countries.